Rancang Bangun Solar Tracker Otomatis Berbasis Mikrokontroler dan Sensor Serat Optik Sebagai Penerima Intensitas Cahaya Maksimum - Syauqi, Farah; Harmadi, Harmadi (Universitas Andalas, 2024)
Solar cell is a device that converts light energy into electrical energy by an effective photovoltaic process. The electrical energy generated by solar cells depends on the intensity of the sun received. The maximum efficiency of solar cells is obtained if it is always perpendicular to the sun, so it is necessary to move the solar cell to follow the movement of the sun. An automatic solar tracker design has been made using fiber optic sensors in this study. The solar tracker design consists of a solar cell and a fiber optic sensor as a sunlight detector consisting of FD-620-10 step-index multimode optical fiber and OPT101 photodetector. The tool that has been made is tested by detecting the voltage, current strength, and power generated by the solar tracker. Solar trackers can produce an average electrical power of 73.79% more optimal than using static solar cells. Based on the results of research, the tool that has been designed can increase the electrical energy generated and store it in accumulators or batteries.